A paper-based SERS assay for sensitive duplex cytokine detection towards the atherosclerosis-associated disease diagnosis. Issue 16 (24th December 2019) - Li, Chunxia; Liu, Yuan; Zhou, Xiaoyan; Wang, Yuling
Abstract : Novel SERS based sensing assay was built by combining nanoporous membrane with sandwich immunoassay for duplex cytokines detection. It can be used as a promising candidate for clinical application due to its excellent performance in human serum. Abstract : Atherosclerosis (AS) is the most common factor causing many cardiovascular and cerebrovascular diseases and has received considerable attention. The occurrence mechanism of AS is uncertain because it is a choronically pathological process that is influenced by multi-aspects, among which cytokines play the key roles in regulating the processes of the immune system. For example, two key cytokines, namely, IL-10 and MCP-1 (chemokine), which are involved in AS progression with varied levels, can be used for AS status monitoring and early diagnosis of AS-associated diseases. Hence, a new paper-based, surface-enhanced Raman spectroscopy (SERS) sensing platform was established for the detection of these two key cytokines. By combining a nanoporous networking membrane as the substrate and SERS nanotags as the probe for signal reading, together with a sandwich design, sensitive and specific identification and quantification of cytokine targets in human serum were achieved with excellent sensing characteristics. The lowest detectable concentration was determined to be 0.1 pg mL −1 for both IL-10 and MCP-1 in human serum. The assay also exhibits high specificity towards target cytokine detection, with low-nonspecific binding and acceptable cross-reactivity in the presence of other structurally similar targets. Finally, the practicability was validated by performing duplex detection in human serum, which further demonstrates the high specificity of the assay for the detection of target cytokines. Taken together, these promising results illustrate that this developed sensing assay is a candidate for clinical multi-target analysis in real environments.